Depositional architectures and sedimentation processes in strike-slip extensional basins: Examples from the Oligocene of the Liaodong Bay Sub-basin, Bohai Bay Basin, China. (January 2021) - Liu, Lei; Chen, Hongde; Zhong, Yijiang; Wang, Jun; Du, Xiaofeng; Zou, Hao
Abstract: The tectonic histories of continental rift basins tend to be complex, with several episodes of subsidence, extensional and strike-slip tectonic activity and diverse paleogeographic characteristics. Intrabasinal and extrabasinal source areas influence deposition resulting in several sedimentary episodes and depositional architectures. In this study, we use 3D seismic data covering Liaodong Bay and well-logging data to analyze sediment source area, paleo-valleys, and slopes to determine the characteristics, distribution and relationships between the source, transport, and sedimentary systems in the Liaodong Bay Sub-basin, which is an Oligocene strike-slip extensional basin with two regional extrabasinal source areas and a local intrabasinal source area in the basin fill succession. Four types of basin-marginal fluvial paleo-valleys are identified in the Liaodong Bay Sub-basin including incised V-, bifurcate V-, wide V- and shallow V- types. The energy of current decreased successively from incised V-, to bifurcate V-, to wide V-type valleys, which ultimately evolved to become shallow V- type during the late stages of a rift lake basin. These sedimentary systems are grouped into five extrabasinal and two intrabasinal types with diverse depositional architectures, based on their slope shapes. The sedimentation processes of the Liaodong Bay Sub-basin were influenced by the tectonic activity, paleogeomorphology and climate condition during the different stages of the strike-slip extensional basin and controlled the accumulation of sandy sediments. Highlights: 3D seismic data and well-logs were analyzed. Depositional architectures of five extrabasinal and two intrabasinal sedimentary systems have been identified. Sedimentation processes and main controlling factors during the Oligocene in the Liaodong Bay Sub-basin have been studied.